Da Vinci's code - Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 2006)
National Geographic travels the world to uncover evidence to support and refute the claims of the best-selling title and in addition interviews other conspiracy theorists that believe Jesus' descendants walk the Earth today.
Title from container.
Not rated.
DVD, region 1; Dolby Digital.
Closed-captioned
Keywords: Jesus Christ -- Family; Mary Magdalene, -- Saint; Leonardo, -- da Vinci, -- 1452-1519.; Video recordings for hard of hearing people; Documentary videos; Documentary -- Feature